Silymarin Reduces Profibrogenic Cytokines and Reverses Hepatic Fibrosis in Chronic Murine Schistosomiasis - Mata-Santos, Hílton Antônio (American Society for Microbiology, 2014)
In chronic schistosomiasis, hepatic fibrosis is linked to the portal hypertension that causes morbidity in Schistosoma mansoni infection. Silymarin (SIL) is a hepatoprotective and antioxidant medicament largely prescribed against liver diseases that has previously been shown to prevent fibrosis during acute murine schistosomiasis. Here we employed silymarin to try to reverse established hepatic fibrosis in chronic schistosomiasis. Silymarin or vehicle was administered to BALB/c mice every 48 h, starting on the 40th (80 days of treatment), 70th (50 days), or 110th (10 days) day postinfection (dpi). All mice were sacrificed and analyzed at 120 dpi. Treatment with silymarin reduced liver weight and granuloma sizes, reduced the increase in alanine aminotransferase and aspartate aminotransferase levels, and reduced the established hepatic fibrosis (assessed by hydroxyproline contents and picrosirius staining). Treatment with silymarin also reduced the levels of interleukin-13 (IL-13) in serum and increased the gamma interferon (IFN-γ)/IL-13 ratio. There was a linear correlation between IL-13 levels in serum and hydroxyproline hepatic content in both infected untreated and SIL-treated mice, with decreased IL-13 levels corresponding to decreased hydroxyproline hepatic contents. Treatment with either SIL or N-acetylcysteine reduced both proliferation of fibroblast cell lines and basal/IL-13-induced production of collagen I, indicating that besides inhibiting IL-13 production during infection, SIL antioxidant properties most likely contribute to inhibition of collagen production downstream of IL-13. These results show that silymarin interferes with fibrogenic cytokines, reduces established fibrosis, and inhibits downstream effects of IL-13 on fibrogenesis, indicating the drug as a safe and cheap treatment to liver fibrotic disease in schistosomiasis.